2015
DOI: 10.1371/journal.pone.0132118
|View full text |Cite
|
Sign up to set email alerts
|

Association between Visit-to-Visit Glucose Variability and Cognitive Function in Aged Type 2 Diabetic Patients: A Cross-Sectional Study

Abstract: Background and PurposeDiabetes is associated with cognitive decline as well as the development of dementia. Although mean blood glucose levels are typically used to assess the status of diabetic patients, glucose variability is also involved in the manifestation of macro- and microvascular complications in this population. Thus, the present study sought to determine whether visit-to-visit glucose variability contributes to cognitive decline in patients with type 2 diabetes.MethodsThe present study assessed 68 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 35 publications
(36 reference statements)
3
32
0
4
Order By: Relevance
“…Postprandial hyperglycemia has also been associated with an increase in the risk of cognitive dysfunction [40,41], and pancreatic, colorectal and breast cancers [42][43][44]. A recent study of 68 individuals with type 2 diabetes revealed that the mean 2-hour PPG value (univariable analysis), and "visit-to-visit" 2-hour PPG variability (multivariable analysis) was associated with cognitive decline in standardized tests over a median 4.8-year period [41].…”
Section: Ppg and Risk Of Cognitive Dysfunction And Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…Postprandial hyperglycemia has also been associated with an increase in the risk of cognitive dysfunction [40,41], and pancreatic, colorectal and breast cancers [42][43][44]. A recent study of 68 individuals with type 2 diabetes revealed that the mean 2-hour PPG value (univariable analysis), and "visit-to-visit" 2-hour PPG variability (multivariable analysis) was associated with cognitive decline in standardized tests over a median 4.8-year period [41].…”
Section: Ppg and Risk Of Cognitive Dysfunction And Cancermentioning
confidence: 99%
“…A recent study of 68 individuals with type 2 diabetes revealed that the mean 2-hour PPG value (univariable analysis), and "visit-to-visit" 2-hour PPG variability (multivariable analysis) was associated with cognitive decline in standardized tests over a median 4.8-year period [41]. PPG levels also correlated with cancer mortality.…”
Section: Ppg and Risk Of Cognitive Dysfunction And Cancermentioning
confidence: 99%
“…There is growing evidence that DM carries greater risks of cognitive decline and dementia compared with healthy individuals . Studies have reported that hyperglycemia, hypoglycemic episodes, postprandial glucose excursions and glucose variability might contribute to cognitive impairment and brain atrophy in individuals with DM . In addition to cerebrovascular diseases, several mechanisms, such as impaired neuronal insulin signaling, inflammation, mitochondrial dysfunction and oxidative stress, β‐amyloid accumulation, and tau phosphorylation, have been proposed for neuronal damage associated with DM .…”
Section: Discussionmentioning
confidence: 99%
“…При изучении гликемического контроля у 337 пациентов пожилого возраста с СД2 с помощью НМГ выявлено, что женский пол, продолжительность диабета, уровень гликированного гемоглобина являются значимыми фак-торами влияния на вариабельность гликемии, в то время как сам по себе возраст не имеет ассоциации с вариабель-ностью гликемии у данных пациентов [28]. Тем не менее, высокая вариабельность гликемии -более значимый показатель неблагоприятного воздействия диабета на когнитивную функцию пожилых лиц, чем средний уро-вень гликемии [29]. В исследовании китайских ученых показана положительная прямая связь между высокой вариабельностью гликемии и наличием и тяжестью сердечно-сосудистых заболеваний (ССЗ) у пациентов с СД2 [30].…”
Section: особенности клинического течения сд2 у пожилыхunclassified